Efektivitas Konseling Kelompok Dengan Teknik Cognitive Restructuring (CR) Untuk Menurunkan Perilaku Bullying Pada Siswa SMP Plus Nurul Hikmah Pamekasan - Hasanah, Iswatun (JKI (Jurnal Konseling Indonesia), 2018)
The purpose of this research is to know effectiveness of group counseling by using Ã¢â‚¬Å“cognitive restructuringÃ¢â‚¬Â technique to reduce Ã¢â‚¬Å“bullyingÃ¢â‚¬Â habit of the students of SMP Plus Nurul Hikmah Pamekasan. The subject of this research is the students of SMP Plus Nurul Hikmah Pamekasan which is showing Ã¢â‚¬Å“bullyingÃ¢â‚¬Â Habit (N=6). The kind o the research that is used quasi experiment designed in One Group pretest posttest design, it is an experiment that conducted only to one group without compared group whit bullying scale as data collection instrument arranged by researcher based on theory and has been tested for its validity and reliability. Data analysis that is used in this research is statistic test wilcoxon and the result of this research that is done analyzed by using statistic test wilcoxon by value asymp sig=0,046 (coefficient level P<0,05) and Z arithmetic = 1,997 could be concluded that a group counseling by using cognitive restructuring is effective to reduce bullying habit of SMP Plus Nurul Hikmah Pamekasan.